2021
DOI: 10.3390/ijerph18073419
|View full text |Cite
|
Sign up to set email alerts
|

MBTI Personality Types of Korean Cabin Crew in Middle Eastern Airlines, and Their Associations with Cross-Cultural Adjustment Competency, Occupational Competency, Coping Competency, Mental Health, and Turnover Intention

Abstract: The purposes of this study were (1) to identify MBTI (Myers–Briggs Type Indicator) personality profiles of Korean cabin crew in Middle Eastern airlines, (2) to determine whether MBTI personality affects their cross-cultural adjustment competency, occupational competency, and coping competency, and (3) to analyze the impact of these variables on their mental health and turnover intention. Furthermore, we verified (4) the moderating effect of cabin crew’s previous overseas experience on the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…In single-centered studies, where demographic characteristics are generally similar, the perception of professional competence does not vary based on these factors. However, in multicenter studies, professional competence levels significantly differ based on demographic characteristics [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In single-centered studies, where demographic characteristics are generally similar, the perception of professional competence does not vary based on these factors. However, in multicenter studies, professional competence levels significantly differ based on demographic characteristics [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang [ 44 ] found a significant correlation that lies between the understanding of social support, career adaptation, and mental health of new graduate students. Studies have also shown that people with higher stress coping, and cross-cultural adaptation are more likely to have positive mental health disposition [ 74 ]. In the indirect effects of this study, it found that the negative effect of learning career adaptation on anxiety was more obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that work stress negatively affects employee capabilities [ 34 , 35 ] and career development behaviors [ 36 , 37 ]. Additionally, a negative empirical relationship has been examined between employee capabilities and turnover intentions [ 38 , 39 ]; likewise, career development behaviors diminished turnover intentions [ 40 , 41 , 42 ]. Although, the relationship between specific factors has been examined, the relationships between work stress, capabilities, career development behavior, and turnover intention are not clear synthetically.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…When it comes to work stress and gender, previous studies have focused on which gender is more vulnerable to work stress. Some studies found that female workers experience more stress than men [ 37 , 38 ], while others reported no difference between gender [ 39 ]. However, the difference in coping with stress at work between female and male workers has not been focused on.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%